20.2k views
1 vote
21....................

21....................-example-1
User JimZer
by
5.6k points

2 Answers

5 votes

Answer:

b.
(d^(5))/(2√(c) )

Explanation:

The given expression is


\frac{√(c^2d^6) }{\sqrt{4c^3d^(-4)} }

We simplify the radicand using the property;
(a^m)/(a^n) =a^(m-n)


\frac{\sqrt{d^(6--4)} }{\sqrt{4c^(3-2)} }


\frac{\sqrt{d^(10)} }{\sqrt{4c^(1)} }


(d^(5))/(2√(c) )

User Sanjeev S
by
6.1k points
4 votes

Answer:

The answer is (b) ⇒
(d^(5) )/(2√(c) )

Explanation:


\frac{\sqrt{c^(2)d^(6)}}{\sqrt{4c^(3)d^(-4)}}

∵ √x² = x ⇒ that means to cancel the square root divide

the power by 2


\sqrt{c^(2)d^(6)}=cd^(3)

∵ √4 = 2 ⇒ √2×2 = √2² = 2

∵ √c³ =
c^{(3)/(2)}


\sqrt{4c^(3)d^(-4)}=2c^{(3)/(2)}d^(-2)


\frac{cd^(3)}{2c^{(3)/(2)}d^(-2)}

∵ In the same base with multiplication we add the power,

in same base with division we subtract the power


(1)/(2)c^{1-(3)/(2)}d^(3-(-2))=(1)/(2)c^{(-1)/(2)}d^(5)=


\frac{d^(5)}{2c^{(1)/(2)}}=(d^(5))/(2√(c))
c^{(1)/(2)}=√(c)

∴ The answer is (b) ⇒
(d^(5))/(2√(c))

User Antonicg
by
5.3k points